How Much and What Kind? Identifying an Adequate Technology Infrastructure for Early Childhood Education - Daugherty, Lindsay (RAND Corporation, 2014)
To realize the potential benefits of technology use in early childhood education, and to ensure that technology can help to address the digital divide, providers, families of young children, and young children themselves must have access to an adequate technology infrastructure that allows them to perform all the tasks and functions that flow from goals for technology use. The authors examine how stakeholders might collaborate to define what constitutes an adequate technology architecture and help ensure it is realized.